Analysis of the motivational factors of FitDance® practitioners in Brazilian health club - Pires, Thamires Sabino (2020)
Gymnastics and dance classes can be an excellent tool in combating physical inactivity, promoting a healthier lifestyle for practitioners. FitDance® is a modality with a fun and relaxing class, I which the teacher develops choreographies together with students. This study aimed to verify the motivational factors for the practice of FitDance® in gyms in a Brazilian city, as well as to verify possible differences in motivational factors among women of different age groups. The sample consisted of 89 women, aged 18 to 50 years old, who had been practising FitDance® for at least one year.  Participants answered the Exercise Motivations Inventory-2 and a sociodemographic questionnaire. The results indicate that the motivational factors Competition (p = 0.003, η2 = 0.28) and Health Rehabilitation (p = 0.021, η2 = 0.22) showed significant differences between women aged 21 to 30 years (Group 1) compared to those aged 41 to 50 years (Group 3). Younger age women seem to be more motivated by competitiveness. On the other hand, older women have greater motivation in relation to Health Rehabilitation. We conclude that FitDance® is a highly motivating modality, regardless of the age group.